LECTINS IN THE INVESTIGATION OF RENAL PATHOLOGIES - Lutsyk, A.D.; Yashchenko, A.M.; Chelpanova, I.V.; Ambarova, N.A. (World of Medicine and Biology, 2022)
Carbohydrate-rich biopolymers – glycoproteins and proteoglycans – play an extremely important role in renal histophysiology. In particular, glycoproteins podoplanin and podocalyxin of podocytes maintain the morpho-functional status of these cellular elements: formation of pedicels, slit diaphragms, and, together with the glomerular membrane – a negative electrical charge and selective permeability of the filtration barrier. Proximal tubules brush border glycoproteins megalin and kubilin are in charge of endocytosis and reabsorption of macromolecules from the ultrafiltrate. Glycoproteins of extracellular matrix – fibronectin, laminin, tenascin, nidogen, various types of collagen, heparan-sulfate proteoglycans perlecan and agrin, dermatan-sulfate proteoglycans versican, biglycan and decorin provide adhesive, mechanical support and inductive properties of renal micro- and ultrastructures. Therefore, lectins as reagents capable of selective recognition of specific glycoepitopes proved to be a valuable tool in the investigation of both normal renal morphogenesis and pathogenesis of nephropathies. Special attention is paid to modern trends in lectinology – investigation of endogenous lectins of humans and animals and their role in health and disease. Practical examples of lectins application as selective histological markers of renal structures are depicted.